The Relationship between Financial Service Innovation and the Performance of Commercial Banks in Thailand: ความสัมพันธ์ระหว่างนวัตกรรมการให้บริการทางการเงิน กับผลการดำเนินงานของธนาคารพาณิชย์ในประเทศไทย - Nittayakamolphun, Pitipat; Bejrananda, Thanchanok; Autchariyapanitkul, Kittawit; Kuson, Siwarat (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การพัฒนาระบบการเงินเป็นสิ่งสำคัญต่อการเจริญเติบโตทางเศรษฐกิจของทุกประเทศ โดยเฉพาะประเทศกำลังพัฒนา ซึ่งนวัตกรรมการให้บริการทางการเงินสามารถยกระดับบริการทางการเงินของธนาคารพาณิชย์ให้มีประสิทธิภาพ และตอบสนองความต้องการของลูกค้าได้มากขึ้น ในขณะเดียวกันต้นทุน รวมไปถึงการแข่งขันของธนาคารพาณิชย์ก็มีมากขึ้น ดังนั้นการศึกษาในครั้งนี้จึงวิเคราะห์ความสัมพันธ์ระหว่างนวัตกรรมการให้บริการทางการเงินกับผลการดำเนินงานของธนาคารพาณิชย์ในประเทศไทยด้วยแบบจำลองเวกเตอร์ อัตรถดถอย (VAR) โดยใช้ข้อมูลอนุกรมเวลารายเดือน ตั้งแต่ปี พ.ศ. 2553 ถึง 2562 ซึ่งพบว่านวัตกรรมการให้บริการทางการเงินทำให้ผลการดำเนินของธนาคารพาณิชย์ในประเทศไทยดีขึ้นอย่างมีนัยสำคัญ ด้วยเหตุนี้ธนาคารพาณิชย์ควรผลักดันให้เกิดการใช้นวัตกรรมการให้บริการทางการเงินเพิ่มขึ้น รวมไปถึงผู้กำหนดนโยบายควรส่งเสริมให้เกิดการพัฒนานวัตกรรมการให้บริการทางการเงิน เพื่อเพิ่มขีดความสามารถในการแข่งขันของภาคการเงินไทย ABSTRACT Development in the financial system is essential to the country’s economy, especially in developing countries. Financial service innovations can enhance both commercial banks’ services and customers’ needs effectively with increasing cost and competition. Thus, this study was conducted in order to analyze the relationship between financial service innovation and the performance of commercial banks in Thailand using the vector autoregressive model (VAR). Monthly time series data during the years 2010 to 2019 were used for analysis. The analysis revealed that financial service innovations have significantly improved the performance of commercial banks in Thailand. For this reason, commercial banks should encourage greater investment in financial service innovation. Additionally, policymakers should foster the development of financial service innovation in order to increase the competitiveness of the financial sector in Thailand.